IMPLEMENTASI PEMBERIAN KREDIT PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PEDESAAN DALAM MENINGKATKAN PENDAPATAN MASYARAKAT USAHA MIKRO, KECIL DAN MENENGAH DI KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - KARYANTI, TRI; Johan, Rina Selva; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACKPNPM'S present independent was intermediated by society expected gets to help entrepreneurs little in get credit with procedural one is easily, easy stipubting and achievable flower. So gets to expand its effort that its income increases. To the effect main from PNPM rural Independent is subject to be increase it welfare and indigent society job chance at rural with push independence in decision making and development management so gets to reach tall resident growth and SDM is qualified. Mark sense PNPM independent rural at district scope in particular district Siak little is expected gets to give benefit to society in particular little entrepreneur in settle problem about capital which is caused doesn't particularly since hard up but then also kekurangmampuan in bring off money that they has. and revenue enhancement effort so gets to secede from poverty and economic social difference and gets to add job chance for society. Government wants that this faction society can increase life level so will increase perkapita's income state who will get to advance state.To the effect this research To know how little entrepreneur income afters gets credit help from PNPM rural Independent. One that as sample in observational it is 68 person. Method that is utilized Descriptive quantitative. Analisis is data utilizes To paired sampel t test.Of processing pickings can be known that PNPM MP has influence to society income.Keyword: PNPM MP, Society Income